Evaluation of radiographic fracture position 1 year after variable angle locking volar distal radius plating: a prospective multicentre case series. (June 2017) - Teunis, T.; Jupiter, J.; Schaser, K. D.; Fronhöfer, G.; Babst, R.; Langer, M.; Platz, A.; Schierz, A.; Joeris, A.; Rikli, D.
Treatment with a variable angle locking plate can, in theory, maintain near anatomic reduction of intra-articular distal radius fractures, but it is unknown to what extent reduction is maintained as measured by computed tomography. We assessed changes in radiographic fracture position 1 year post-operatively. We included 73 patients of whom 66 patients (90%) had radiographs available for review at 1 year post-operatively. We found a small (less than 2 mm or 2°) but statistically significant change in several measures. Accounting for inter-observer variability, this is probably within measurement error. We found no difference in change in fracture position or range of motion, grip strength or patient-reported outcome between the use of one or two distal rows of screws. Our results show that minimal changes in reduction can be expected after volar plate fixation in most patients. We recommend using only one screw row routinely, limiting costs, surgical time and the risk of misplacement of screws. Level of evidence: IV